Polyphenol-rich extract from grape and blueberry attenuates cognitive decline and improves neuronal function in aged mice - Julien Bensalem; Stéphanie Dudonné; David Gaudout; Laure Servant; Frédéric Calon; Yves Desjardins; Sophie Layé; Pauline Lafenetre; Véronique Pallet (Journal of Nutritional Science, 2018)
Ageing is characterised by memory deficits, associated with brain plasticity impairment. Polyphenols from berries, such as flavan-3-ols, anthocyanins, and resveratrol, have been suggested to modulate synaptic plasticity and cognitive processes. In the present study we assessed the preventive effect of a polyphenol-rich extract from grape and blueberry (PEGB), with high concentrations of flavonoids, on age-related cognitive decline in mice. Adult and aged (6 weeks and 16 months) mice were fed a PEGB-enriched diet for 14 weeks. Learning and memory were assessed using the novel object recognition and Morris water maze tasks. Brain polyphenol content was evaluated with ultra-high-performance LC-MS/MS. Hippocampal neurotrophin expression was measured using quantitative real-time PCR. Finally, the effect of PEGB on adult hippocampal neurogenesis was assessed by immunochemistry, counting the number of cells expressing doublecortin and the proportion of cells with dendritic prolongations. The combination of grape and blueberry polyphenols prevented age-induced learning and memory deficits. Moreover, it increased hippocampal nerve growth factor (Ngf) mRNA expression. Aged supplemented mice displayed a greater proportion of newly generated neurons with prolongations than control age-matched mice. Some of the polyphenols included in the extract were detected in the brain in the native form or as metabolites. Aged supplemented mice also displayed a better survival rate. These data suggest that PEGB may prevent age-induced cognitive decline. Possible mechanisms of action include a modulation of brain plasticity. Post-treatment detection of phenolic compounds in the brain suggests that polyphenols may act directly at the central level, while they can make an impact on mouse survival through a potential systemic effect.